2005
DOI: 10.1248/cpb.53.989
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of C3-C12 Dihydropyran Portion of Antitumor Laulimalide Using Copper-Catalyzed Oxonium Ylide Formation-[2,3] Shift

Abstract: Tetrahydropyran and dihydropyran rings are structural components of a large number of natural products.1,2) Therefore, considerable attention has recently been directed toward their stereoselective synthesis. [3][4][5][6][7][8] The microtubule-stabilizing agent (Ϫ)-laulimalide, 9-18) also known as fijianolide B, which was isolated from several sponges (Cacospongia mycofijiensis,19) Hyattella sp., 20) Fasciospongia rimosa 21) ), contains 2,6-trans disubstituted 5,6-dihydro-2H-pyran as its C5-C9 portion. Stereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…8 The X-ray analysis of 10 confirmed the trans relationship between the 5-silyloxymethyl and 2-allyl groups and showed the 3,4-cis stereochemistry. This indicated that the rhodium(II)-catalyzed reaction proceeds via oxonium ylide A, which is apparently a more stable intermediate than B, and that the subsequent [2,3]-sigmatropic rearrangement of the allyl group from oxygen to carbon formed 3, consistent with our previously reported stereoselectivity for the reaction of 5-allyloxy-2-diazo-3-ketoesters (Scheme 4). In the subsequent reduction, the hydride should attack the carbonyl group from the α-side to avoid the adjacent bulky α-TBDMSO group of ketone to give β-hydroxy compound 9.…”
Section: Figure 1 Cinatrin Familysupporting
confidence: 89%
See 4 more Smart Citations
“…8 The X-ray analysis of 10 confirmed the trans relationship between the 5-silyloxymethyl and 2-allyl groups and showed the 3,4-cis stereochemistry. This indicated that the rhodium(II)-catalyzed reaction proceeds via oxonium ylide A, which is apparently a more stable intermediate than B, and that the subsequent [2,3]-sigmatropic rearrangement of the allyl group from oxygen to carbon formed 3, consistent with our previously reported stereoselectivity for the reaction of 5-allyloxy-2-diazo-3-ketoesters (Scheme 4). In the subsequent reduction, the hydride should attack the carbonyl group from the α-side to avoid the adjacent bulky α-TBDMSO group of ketone to give β-hydroxy compound 9.…”
Section: Figure 1 Cinatrin Familysupporting
confidence: 89%
“…However, the deprotection was achieved by the treatment of 17 with iodine in methanol 11 under reflux to give 2-epi-cinatrin C 1 dimethyl ester 2 12,13 in 84% yield. In conclusion, the Rh 2 (OAc) 4 -catalyzed oxonium ylide formation- [2,3]-sigmatropic rearrangement reaction of α-diazo-β-keto ester 4 derived from D-glucose stereoselectively proceeded to give tetrahydrofuran-3-one 3 as a single diastereomer in high yield. The resulting 3 was converted into 2-epi-cinatrin C 1 dimethyl ester 2.…”
Section: Figure 1 Cinatrin Familymentioning
confidence: 90%
See 3 more Smart Citations